PENINGKATAN PROSES BELAJAR MELALUI DUKUNGAN PERHATIAN ORANG TUA SERTA SUASANA RUMAH DAN FASILITAS BELAJAR - Handoko, Bobi; Fetri Hrp, Dian; Pracillia, Citra; Sipahutar, Romaida (LPPM Universitas Awal Bros, 2024)
The family environment and children influence each other in the teaching and learning process. Parental attention, family economic conditions, home atmosphere, and learning facilities play an important role in shaping student learning outcomes. This study aims to investigate the influence of these factors on the learning process of grade III students at SMKN 3 Pekanbaru. A qualitative survey research design was used, involving 51 students selected through random sampling. Data was collected using questionnaires and analyzed using statistical data processing applications.. The results revealed positive, negative, and significant relationships between the factors studied and the learning process. Positive and significant factors such as parental attention, home atmosphere and learning facilities can improve students' learning process, while negative factors such as family economic conditions can hinder learning. The family environment has a positive, negative and significant influence. This should be a concern for parents in educating, guiding, providing learning facilities, and paying attention to their children. The linear equation model resulting from data analysis is Y= 0,275 – 0,139 + 0,159 + 0,536 + 0,060.